Laparoscopic cholecystectomy: clinical and patient reported outcomes - Daliya, Prita (2020)
Introduction: Laparoscopic cholecystectomy is one of the commonest general surgical operations performed, yet little is known about its impact on patient and clinical outcomes in the UK (United Kingdom) population. Where available, existing processes for measuring outcomes are not readily accessible or unable to provide real-time information to end users. Despite technological advances, there have been no significant changes in improving the communication and data-sharing processes between patients and clinicians. The aims of this study were to use Hospital Episode Statistics (HES) data to identify the burden of disease leading to cholecystectomy in the UK population, help develop the patient-facing application aboutmyop.org and pilot its use in routine clinical care for patients undergoing elective laparoscopic cholecystectomy.